Rewang as a Third Space for Negotiating Puritan Islam and Javanese Tradition in Laweyan, Surakarta - Ronald Tri Pamungkas; Muhamad Faturahman; Muhammad Rizal Hifandi Jusuf; Mirza Hamsadarma; Faris Mutaz Hamid (Kopertais Wilayah III Yogyakarta, 2026)
Abstract This research aims to analyze the role of the rewang tradition as a third space in creating social harmony amidst differing religious views regarding the tahlilan ritual in Javanese society, with a case study in Kampung Batik Laweyan. The background of the research is based on the tension between groups that accept and reject tahlilan, which is considered bid'ah by some circles, as well as the strong influence of local culture within the Javanese social structure. Using a qualitative method with an intrinsic case study approach, data were obtained through in-depth interviews and documentation in Laweyan, whose community is institutionally dominated by Muhammadiyah but continues to preserve the practice of tahlilan. The results of the research show that rewang, as a practice of mutual cooperation in food preparation for events, functions as a neutral third space, allowing for the negotiation of hybrid identities and practical coexistence without resolving theological differences. This space is dominated by female agency, which through concrete actions and non-verbal communication, succeeds in reducing potential conflict and maintaining social cohesion. These findings enrich the application of the Third Space theory (Bhabha) in intra-religious and intra-cultural contexts, while simultaneously asserting that social harmony is often built through everyday practical spaces, rather than through discursive resolution. Although effective, the sustainability of this third space is vulnerable to pressure from formal religious authorities, generational change, and the process of commodification. Keywords: third space, rewang, tahlilan, social harmony, hybridity, Javanese culture.